Perceived Burdensomeness, Thwarted Belongingness, and Social Exclusion in Transgender Women: Psychometric Properties of the Interpersonal Needs Questionnaire - Liu, Yujie; Wang, Rongxi; Chang, Ruijie; Wang, Huwen; Xu, Lulu; Xu, Chen; Yu, Xiaoyue; Liu, Shangbin; Chen, Hui; Chen, Yingjie; Jin, Lian; Wang, Ying; et al. (Frontiers in Psychology, 2022)
Transgender women (TGW) experience serious psychiatric problems and high suicide rates. According to the interpersonal theory of suicide, thwarted belongingness and perceived burdensomeness play major roles in suicidality and can be measured by the Interpersonal Needs Questionnaire (INQ). However, no study has validated the use of the INQ in TGW. This study aimed to examine the psychometric properties of the INQ among TGW. We recruited 198 TGW (mean age 38.47 years) from Shenyang, China using snow-ball sampling. The construct validity of the INQ was assessed through factor analysis, and convergent and divergent validity was examined through a structural equation model with other psychosocial factors. The construct validation analysis supported a three-factor model (perceived burdensomeness, thwarted belongingness and social exclusion) with satisfactory fit indices: χ2 / df = 1.26, RMSEA = 0.036, CFI = 0.967, TLI = 0.960, SRMR=0.047. The thwarted belongingness was significantly associated with self-esteem and social support, the social exclusion was significantly associated with loneliness, depression, entrapment and defeat, suggesting satisfactory convergent and divergent validity for the three-factor model. The present findings indicate that for TGW, high social exclusion is important in assessing perceived interpersonal needs, while the notable deviation from previous two-factor model warrants further study.